Optimum Workspace Design in A Plug Assembly Line - Adi , Saptari; Seri Rahayu , Kamat; Wan Hasrulnizzam , Wan Mahmood; Isa, Halim (2007)
In most industry, assembly line job environments such as workstation design is one of key factors contribute to workers’ performance. Workstation design such as: standing or sitting, the use of tools such as jig and the height of working table are influencing worker’s productivity. This research is an attempt to investigate the effect workstation design factors to assembly time. Workstation factors include Workers, Position: standing or sitting, Table-height, and Tools: with Jig and without Jig to assemble an electrical appliance (a plug). Design of experiment of 24 i.e. two level of each factors is used. Two subjects were employed to conduct the experiments. 36 experiments for each level of factors were done, 288 experiments for 8 different sets were conducted for each subject. The results show that Tool in this case the use of Jig and Table, have significant effect to the response time (assembly time) and interaction of three factors: Tool, Table, and Position have significant influence on the assembly time.